Intrinsic sensitivity of Kir1.1 (ROMK) to glibenclamide in the absence of SUR2B. Implications for the identity of the renal ATP-regulated secretory K+ channel. - Konstas, A; Dabrowski, M; Korbmacher, C; Tucker, S (2002)
The precise molecular identity of the renal ATP-regulated secretory K+ channel is still a matter of some controversy. The inwardly rectifying K+ channel, Kir1.1 (ROMK) appears to form the pore of the channel, and mutations in Kir1.1 are responsible for Bartter syndrome. The native channel is sensitive to inhibition by the sulfonylurea glibenclamide, and it has been proposed that an accessory protein is required to confer glibenclamide sensitivity to Kir1.1. Several recent studies have suggested that the native channel is composed of the splice variant Kir1.1b (ROMK2) and the sulfonylurea receptor isoform SUR2B and that there is a direct physical interaction between these subunits. In this study, we have monitored the interaction between Kir1.1b and SUR2B. We find that SUR2B reaches the plasma membrane when coexpressed with Kir6.1 or Kir6.2 but not when coexpressed with Kir1.1b. Furthermore, we find that Kir1.1b exhibits an intrinsic sensitivity to inhibition by glibenclamide with an affinity similar to the native channel. These results demonstrate that SUR2B does not traffic to the membrane in the presence of Kir1.1b and is not required to confer glibenclamide sensitivity to Kir1.1b. This has important implications for the presumed structure of the renal ATP-regulated secretory K+ channel.